(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Volleyball Game requires comprehensive ability including physical, technical, mental andtactical abilities. Among them physical abilities of players exert marked effects on the skills of theplayers themselves and the tactics of the team. A volleyball match provides a dazzling workout for theplayers’ bodies because they constantly alternate between short bursts of high-intensity movements likejumping and spiking low-intensity movements. Therefore, the athletes should have strong anaerobicand aerobic capacities. Women professional and nonprofessional players are selected for this sportbased on their skills, performance levels, physique and muscular strength. While team court sports havebeen widely researched, no studies have been conducted on abilities of professional nonprofessionalwomen volleyball players. Moreover, the abilities is biomotor abilities, physiological and anthropometric.the investigator chose speed, strength, flexibility, agility from the many biomotor skills from the manyphysiological factors, resting pulse rate, VO2 max, mean arterial blood pressure, breath holding timeand from the many anthropometric factors, standing height, weight, arm length, leg length.